Book review: Sound reading. Exploring and conceptualising audiobook practices among young adults - Colbjørnsen, Terje (Nordic Journal of Library and Information Studies, 2022)
Book review of Elisa Tattersall Wallin (2022) Sound reading. Exploring and conceptualising audiobook practices among young adults, Doctoral Thesis University of Borås, Faculty of Librarianship, Information, Education and IT